1999
DOI: 10.1017/s0012162299001358
|View full text |Cite
|
Sign up to set email alerts
|

Brain perfusion SPECT and MRI in foetal alcohol syndrome

Abstract: Six boys and five girls with a mean age of 8.6 (range 3 to 13) years with foetal alcohol syndrome (FAS) were studied by MRI and single photon emission computed tomography (SPECT) to find specific areas of vulnerability. Morphological anomalies shown in six of 11 patients by MRI were situated both cortically and subcortically: cortical atrophy (N = 2), dilated ventricle (N = 1), corpus callosum hypoplasia (N = 1), cerebellar atrophy (N = 2), one of the latter with Arnold-Chiari malformation (N = 1). Delayed mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 30 publications
2
79
0
1
Order By: Relevance
“…Similar to cortical gray matter changes, reductions in white matter volume were observed globally [18;26], as well as around the occipital horns [48], in the left parietal…”
Section: Alterations In White Mattermentioning
confidence: 82%
See 1 more Smart Citation
“…Similar to cortical gray matter changes, reductions in white matter volume were observed globally [18;26], as well as around the occipital horns [48], in the left parietal…”
Section: Alterations In White Mattermentioning
confidence: 82%
“…A large reduction of blood flow in the temporal region relative to the cerebellum was observed in three subjects with FAS, while such reduction was smaller in two healthy subjects [23]. A SPECT study A C C E P T E D M A N U S C R I P T 22 using Tc-99m hexamethylpropyleneamine oxime in children with FAS reported mild hypoperfusion in the left parietooccipital and right frontal region [48]. In another SPECT study using 123 I-nor-β-CIT tracer, children with FASD were reported to have lower serotonin in the medial frontal cortex and higher levels of dopamine transporters in the striatum compared to healthy peers [129].…”
Section: Pet and Spectmentioning
confidence: 99%
“…However, these reductions in hippocampal volume were Alcohol-related effects on the hippocampus 1023 proportional to reductions in overall brain size (Archibald et al, 2001). Additional differences in hippocampal architecture between children with PAE and controls were found by Riikonen et al (1999Riikonen et al ( , 2005, who reported reduced hippocampal volumes and greater hippocampal asymmetry (i.e., left smaller than right) in children with PAE relative to controls, as well as by Autti-Rämö et al (2002), who found left hippocampal thinning in three children with varying levels of PAE. Several studies of PAE in children have used structural MRI to investigate the structure-function correlations between verbal learning and recall and the corpus callosum (Sowell et al, 2001), cerebellum (O'Hare et al, 2005), as well as overall cortical thickness (Sowell et al, 2008).…”
Section: Introductionmentioning
confidence: 92%
“…We hypothesized that the FASD group would show impaired verbal learning, as well as poor verbal and spatial recall. Given earlier findings of left-right hippocampal asymmetries (i.e., smaller left than right volume, Riikonen et al, 1999Riikonen et al, , 2005 and left hippocampal thinning (Autti-Rämö et al, 2002) in children with PAE, we hypothesized that any reductions found in hippocampal volume may be greater in the left than the right hippocampus in children with FASDs. We further hypothesized that spatial recall deficits found in children with FASDs would be more strongly associated with right than left hippocampal volume reductions, based on studies relating poor spatial recall to right hippocampal damage (Bohbot et al, 1998;Uecker & Nadel, 1996).…”
Section: Introductionmentioning
confidence: 98%
“…More specifically, volume and density abnormalities in both the white matter and gray matter have been noted in various brain regions including the corpus callosum, the temporoparietal area, the frontal area, and the basal ganglia. (Archibald et al 2001;Riikonen et al 1999;Sowell et al 2001b;Sowell et al 2002). By using the diffusion tensor imaging (DTI) technique, we recently also found significant difference in the diffusion fractional anisotropy and apparent diffusion coefficient in the corpus callosum of alcohol-affected young adults compared with the non-exposed controls (Ma et al 2005).…”
Section: Introductionmentioning
confidence: 94%